HARMONIZING THE INTERNATIONAL TRADE POLICIES AND THE RIGHT FOR HEALTH PROTECTION MEASURES: CASE STUDY ON WHO DSB RULING ON US-CLOVE CIGARETTES - Dodik Setiawan Nur Heriyanto, SH., MH , Eko Rial Nugroho, SH., MH (MTCC, John Hopkins n The Union, 2016)
is one of the largest manufacturers of tobacco in the world. One specific tobacco product manufactured in Indonesia is clove cigarette that has been popular locally and also marketed abroad. By enacting Family Smoking Prevention and Tobacco Control Act in 2009, the United States bans the production and sale of clove cigarettes yet does not prohibit the production of menthol cigarettes. From this regulation, in 2011, Indonesia requested the Dispute Settlement Body of World Trade Organization (DSB WTO) to stop the ban on Indonesia clove cigarettes sale in the United States due to the inconsistency of the banning to the national treatment obligation under article 2.1 on Technical Barriers to Trade (TBT) agreement. The WTO Panel‟s ruling then upheld by the Appellate Body made their report that the United States regulation that bans clove cigarettes was discriminatory. This ruling is welcomed by Indonesia‟s tobacco business but in other side also gains worldwide critics that the right to health shall be taken into consideration to limit the trade on cigarettes for public health concern. This research tried to analyze the legal effect of WTO DSB ruling on US-Clove Cigarettes and the availability of rights based approach to be used during the judicial making process in DSB WTO to harmonize between the international trade policies and the right for health protection measures. Moreover, this paper suggests that both WTO and WHO shall altogether create single international policy that reflects in achieving the goals of FCTC and the fair trade under WTO regime whatsoever states parties on both organization confidently implementing the rule of FCTC. Keywords: is one of the largest manufacturers of tobacco in the world. One specific tobacco product manufactured in Indonesia is clove cigarette that has been popular locally and also marketed abroad. By enacting Family Smoking Prevention and Tobacco Control Act in 2009, the United States bans the production and sale of clove cigarettes yet does not prohibit the production of menthol cigarettes. From this regulation, in 2011, Indonesia requested the Dispute Settlement Body of World Trade Organization (DSB WTO) to stop the ban on Indonesia clove cigarettes sale in the United States due to the inconsistency of the banning to the national treatment obligation under article 2.1 on Technical Barriers to Trade (TBT) agreement. The WTO Panel‟s ruling then upheld by the Appellate Body made their report that the United States regulation that bans clove cigarettes was discriminatory. This ruling is welcomed by Indonesia‟s tobacco business but in other side also gains worldwide critics that the right to health shall be taken into consideration to limit the trade on cigarettes for public health concern. This research tried to analyze the legal effect of WTO DSB ruling on US-Clove Cigarettes and the availability of rights based approach to be used during the judicial making process in DSB WTO to harmonize between the international trade policies and the right for health protection measures. Moreover, this paper suggests that both WTO and WHO shall altogether create single international policy that reflects in achieving the goals of FCTC and the fair trade under WTO regime whatsoever states parties on both organization confidently implementing the rule of FCTC. Keywords: Trade on cigarette, WTO, and the right for health